Primary haemochromatosis resulting in dilated cardiomyopathy arising out of mutation in HJV gene in Indian patients: a rare scenario. Issue 9 (16th September 2020) - Goyal, Abhishek; Mohan, Bishav; Saggar, Kavita; Wander, Gurpreet Singh
Abstract : Primary haemochromatosis (PH) is a genetic disorder of iron metabolism with multiorgan involvement due to mutations in HFE or more rarely haemojuvelin (HJV) gene. Cardiac involvement results in dilated cardiomyopathy with reduced ejection fraction and progressive heart failure. PH is rarely reported from India and cardiomyopathy due to PH from HJV mutations is thought to be uncommon. We report two families with cardiomyopathy resulting from PH. Diagnosis was suspected on the basis of skin pigmentation, markedly elevated serum ferritin and transferring saturation. Genetic testing revealed a rare mutation in HJV gene in one family. Being a treatable condition, PH should be suspected and investigated in cardiomyopathy patients in Indian subcontinent. If HFE is negative, analysis of non-HFE mutation should always be considered.